The Effect of Pre-strain and Strain Path Changes on Ductile Fracture - Alinaghian, Yaser (Université d'Ottawa / University of Ottawa, 2013)
Industrial metal forming operations generally require several deformation steps in order to create the final product. The mechanical behavior of materials undergoing strain path changes can be very different from those deformed in a given direction to fracture. The work presented here employed laser drilled model materials to better understand the effect of pre-strains and strain path changes on void growth and linkage leading to fracture is studied. The experimental results show that increasing pre-strain results in faster void growth which was justified in terms work hardening rate in the sample. Scanning electron microscope images revealed that the ductility of the sample decreased with increasing pre-strain but only slightly compared to the large decrease in far field strain at failure. This suggests that pre-strain affects strain localization significantly and to a lesser extent the ductility. Finally a finite element model has been built to predict the linkage between voids.
Keywords: Ductile Fracture; Pre Strain; Strain Path Changes; Void growth and coalescence